Brief Exposure to Secondhand Smoke Reversibly Impairs Endothelial Vasodilatory Function - Pinnamaneni, Kranthi (Oxford University Press, 2014)
INTRODUCTION: We sought to determine the effects of brief exposures to low concentrations of tobacco secondhand smoke (SHS) on arterial flow-mediated dilation (FMD, a nitric oxide-dependent measure of vascular endothelial function), in a controlled animal model never before exposed to smoke. In humans, SHS exposure for 30min impairs FMD. It is important to gain a better understanding of the acute effects of exposure to SHS at low concentrations and for brief periods of time. METHODS: We measured changes in FMD in rats exposed to a range of real-world levels of SHS for durations of 30min, 10min, 1min, and 4 breaths (roughly 15 s). RESULTS: We observed a dose-response relationship between SHS particle concentration over 30min and post-exposure impairment of FMD, which was linear through the range typically encountered in smoky restaurants and then saturated at higher concentrations. One min of exposure to SHS at moderate concentrations was sufficient to impair FMD. CONCLUSIONS: Brief SHS exposure at real-world levels reversibly impairs FMD. Even 1min of SHS exposure can cause reduction of endothelial function.